2018
DOI: 10.1007/s11356-018-1698-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions, economic growth, energy use, and urbanization in Saudi Arabia: evidence from the ARDL approach and impulse saturation break tests

Abstract: This study investigates the existence of long-run relationship between CO emissions, economic growth, energy use, and urbanization in Saudi Arabia over the period 1971-2014. The autoregressive distributed lag (ARDL) approach with structural breaks, where structural breaks are identified with the recently impulse saturation break tests, is applied to conduct the analysis. The bounds test result supports the existence of long-run relationship among the variables. The existence of environmental Kuznets curve (EKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 83 publications
5
52
0
2
Order By: Relevance
“…These studies apply ARDL, ARDL bounds, ARDL with structural breaks, VECM Granger Causality, CUSUM, CUSUMSQ, DOLS, FOMLS, and Gregory and Hansen and Hatemi-J approaches. hold. For instance, Raggad (2018), Gill, Viswanathan, and Hassan (2018), , Katircioglu andKatircioglu (2018), andAl-Mulali et al (2018) confirms the non-validity of EKC hypothesis for Saudi Arabia, Malaysia, Pakistan, Turkey, and Kenya respectively. Recently, reveals that coal consumption, oil consumption, economic growth, and natural gas consumption have a positive impact on the environmental degradations in Pakistan both in the short-run and long-run.…”
Section: Related Literaturementioning
confidence: 68%
See 1 more Smart Citation
“…These studies apply ARDL, ARDL bounds, ARDL with structural breaks, VECM Granger Causality, CUSUM, CUSUMSQ, DOLS, FOMLS, and Gregory and Hansen and Hatemi-J approaches. hold. For instance, Raggad (2018), Gill, Viswanathan, and Hassan (2018), , Katircioglu andKatircioglu (2018), andAl-Mulali et al (2018) confirms the non-validity of EKC hypothesis for Saudi Arabia, Malaysia, Pakistan, Turkey, and Kenya respectively. Recently, reveals that coal consumption, oil consumption, economic growth, and natural gas consumption have a positive impact on the environmental degradations in Pakistan both in the short-run and long-run.…”
Section: Related Literaturementioning
confidence: 68%
“…In this nexus, economic growth is both the problem and the solution for environmental degradation. Knowing this solution, many researchers investigated this issue for different countries and regions to tell whether economic growth can be a solution to environmental problems in that country or region (see Raggad, 2018;Bekhet & Othman, 2018;Shahzad, Kumar, Zakaria, & Hurr, 2017). Liobikiene, Mandravickaite, Krepstuliene, Bernatoniene, and Savickas (2017) reveal that none of the Baltic states, including Lithuania, has a clear policy framework for the greenhouse gases (GHG) emission reduction, even though GHG emission reduction is the critical priority in the Lithuanian Sustainable Development Strategy.…”
Section: Introductionmentioning
confidence: 99%
“…They also found Granger causality from income per capita to pollution emissions. Using period 1971-2014, Raggad [32] investigated the EKC hypothesis, and the results indicated that income has a monotonic and positive effect on the CDE. Energy use and urbanization were seen to have a positive and negative impact on CO 2 emissions respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Against this backdrop, numerous research studies have been dedicated to the determinants of emissions both in a single country case (Brizga, Feng, & Hubacek, 2013; Cansino, Román, & Ordonez, 2016; Chin, Puah, Teo, & Joseph, 2018; Mrabet & Alsamara, 2017; Raggad, 2018) and for a group of countries (Balogh & Jámbor, 2017; Dogan & Seker, 2016; Iwata, Okada, & Samreth, 2012; Li & Lin, 2015; Lin, Wang, Marinova, Zhao, & Hong, 2017; Moutinho, Moreira, & Silva, 2015; Sharma, 2011; Shuai et al, 2017; Yeh & Liao, 2017). China and the United States are the two biggest emitters of CO 2 (Liu & Xiao, 2018).…”
Section: Introductionmentioning
confidence: 99%